(untitled) (Eurasian Journal of Philology Science and Education, 2016)
In this scientific article were analyzed lyrical narratives of great writer Azilkhan Nurshaiykhov from ideological heading and imaginative point. A. Nurshaiykhov’s lyrical stories are full of confusing but at the same time interesting tales. People’s passion to live, way of keeping humanity, to be keen on art were highly valued in his books. The majority of his work were dedicated to youth. The people who were given the main parts – full of humanness, with beautiful soul, events – their destiny, the aim – to exhort to humanism. In this case the works such as «Asem» , «Botakoz», «Eki dapter», etc. can be the vivid evidence which were written in varied figurative ways. If we analyze A. Nurshaiykhov’s works in details, we can assure ourselves that the worth is in its content, presentative structure but not in extent. We extract that A. Nurshaiykhov’s works are not great, the greatness is in his deep messages.